2010
DOI: 10.3310/hta14010
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre randomised controlled trial examining the cost-effectiveness of contrast-enhanced high field magnetic resonance imaging in women with primary breast cancer scheduled for wide local excision (COMICE)

Abstract: on behalf of the COMICE Trial GroupHow to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 49 publications
(72 reference statements)
0
70
0
4
Order By: Relevance
“…The criteria for the values that they selected in their analysis were that they would ideally be based on EQ-5D scores, would ideally have been derived from UK patients and these patients would ideally reflect the younger age range of patients in the TARGIT-A trial. The values that they selected, from studies by Turnbull et al 87 and Lidgren et al, 88 were as follows:…”
Section: Utilities and Quality-adjusted Life-yearsmentioning
confidence: 99%
“…The criteria for the values that they selected in their analysis were that they would ideally be based on EQ-5D scores, would ideally have been derived from UK patients and these patients would ideally reflect the younger age range of patients in the TARGIT-A trial. The values that they selected, from studies by Turnbull et al 87 and Lidgren et al, 88 were as follows:…”
Section: Utilities and Quality-adjusted Life-yearsmentioning
confidence: 99%
“…Full data extraction of all the included studies is shown in Appendix 8. The nine studies provided data for five out of the seven health states potentially relevant for the independent model: disease free after WLE (one study), 126 WLE + WB-EBRT (three studies), [127][128][129] disease free after local recurrence (one study), 132 mastectomy and reconstruction (two studies), 130,131 and distant recurrence/ metastatic breast cancer (three studies). 132,133,134 No EQ-5D data were identified for the health states WLE + INTRABEAM or WLE + INTRABEAM + WB-EBRT.…”
mentioning
confidence: 99%
“…132,133,134 No EQ-5D data were identified for the health states WLE + INTRABEAM or WLE + INTRABEAM + WB-EBRT. Out of the nine studies, two studies each were based in the UK, 126,128 the USA, 127,129 and Sweden, 131,132 one study each was based in Canada 130 and Germany, 134 and the remaining study was based on a RCT conducted across the UK and USA. EQ-5D…”
mentioning
confidence: 99%
“…The 2010 UK COMICE trial put the loss in quality of life from surgery in 1625 women with a low risk breast cancer at 5% after 12 months. 12 The five year follow-up to the PRIME trial showed that the quality of life losses after surgery were unchanged after five years. 13 Overall, our assumption of a permanent 6% loss in quality of life from surgery does not seem unreasonable, but more robust estimates are needed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%